2004
DOI: 10.1002/app.20556
|View full text |Cite
|
Sign up to set email alerts
|

A study on the biodegradability of polyethylene terephthalate fiber and diethylene glycol terephthalate

Abstract: ABSTRACT:The degradation of diethylene glycol terephthalate (DTP) and polyethylene terephthalate fiber (PET fiber) by microbes and lipase was studied. The HPLC method was used to determine the degradation ratio and degradation rule of DTP. Greater than 90% DTP was degraded by microbes in 24 days and 40% by lipase in 24 h. The degradation of DTP can be described by the first-order reaction model. Although the biodegradation ratio of PET fiber was still weak, we demonstrated with SEM micrographs and HPLC analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 5 publications
2
49
0
Order By: Relevance
“…Currently, there are three main methods for plastic waste handling: burying in landfill, incineration and recycling [45]. Each has its own inherent limitations.…”
Section: Plastic Disposal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are three main methods for plastic waste handling: burying in landfill, incineration and recycling [45]. Each has its own inherent limitations.…”
Section: Plastic Disposal Methodsmentioning
confidence: 99%
“…The first drawback associated with disposal of plastic waste is the fact that landfill facilities occupy space that could be utilised for more productive means, such as agriculture [45]. This is compounded by the slow degradability of most plastics, as this means the occupied land is unavailable for long periods of time.…”
Section: Landfillmentioning
confidence: 99%
“…Generally, PET was incubated in the enzymatic solution at temperatures between 30 to 60°C for a period of time ranging from 3 to 14 days. Residual PET and solution were separated for product characterization [130][131][132][133]. As shown in Table 1, different enzymes such as saccharomonospora viridis cutinase polyesterase, thermobifidia fusca hydrolase, cutinase and lipase were applied for PET degradation.…”
Section: De-polymerization Of Pet Using Enzymesmentioning
confidence: 99%
“…Donelli et al [132] only studied the surface morphology of PET treated with cutinase and did not make a qualitative or quantitative statement of possible reaction products. In contrast, Zhang et al [133] studied the application of lipase as degrading agent for diethylene glycol terephthalate (DGTP) and PET at 30°C and 14 days. They found that lipase is capable of fully converting DGTP to terephthalic acid (TPA), whereas the degradation of PET to TPA was negligible.…”
Section: De-polymerization Of Pet Using Enzymesmentioning
confidence: 99%
“…This growth aggravates the challenges of waste plastics disposal, especially in remote areas [3]. Landfill and incineration methods induce several negative environmental issues [4][5][6], and this linear model of resource consumption with a "take-make-dispose" pattern has increasingly significant economic limits [7]. To mitigate the contradiction between the rapid economic growth and the shortage of virgin materials and energy, the circular economy was first proposed in 1998 to build up the circular flow of materials and the use of resources and energy through multiple phases [8,9].…”
Section: Introductionmentioning
confidence: 99%